E-demokracija in e-volitve - Gaber, Slavko (Teorija in praksa, 2008)
In an era of the growing importance of ICT the question of e-voting is becoming an important question of future electoral practices. In several countries (Spain, the Netherlands, England, Switzerland, Estonia, France...) e-voting is a legitimate extra opportunity for voting at different levels. The inauguration of e-voting is not radically shifting or widening the scope of representative democracies, yet it seems that particularly its Internet form is a logical and timely addition to classic pencil and paper voting which can slow down the decreases seen in electoral turnouts. As such, Internet voting is also needed in the future development of voting in Slovenia.
Keywords: democracy; demokracija; election; volitve; Slovenia; Slovenija; Estonia; Estonian Soviet Socialist Republic; Estonija; Switzerland; Švica; tajno glasovanje; elektronsko glasovanje; e-volitve; e-demokracija